2018
DOI: 10.1007/s10620-018-4958-y
|View full text |Cite
|
Sign up to set email alerts
|

Left-Sided Colectomy: One of the Important Risk Factors of Metachronous Colorectal Adenoma After Colectomy for Colon Cancer

Abstract: The LCR group had a higher adenoma recurrence rate than the RCR group. Further studies are required to determine the optimal surveillance intervals according to the type of colonic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
1
13
2
Order By: Relevance
“…Considering this, we excluded patients with rectal cancer and only patients with colon cancer above the rectosigmoid junction were included in the present study. Even after excluding patients with rectal cancer, distal colon cancer remains an independent risk factor for metachronous colon neoplasms, which was consistent with findings in previous studies [12,13,17,21].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Considering this, we excluded patients with rectal cancer and only patients with colon cancer above the rectosigmoid junction were included in the present study. Even after excluding patients with rectal cancer, distal colon cancer remains an independent risk factor for metachronous colon neoplasms, which was consistent with findings in previous studies [12,13,17,21].…”
Section: Discussionsupporting
confidence: 92%
“…In this present study, the incidence of metachronous adenomas (63.8%) is higher than that in previous reports (25% to 48%) [9][10][11]. One possible explanation is the relatively longer follow-up period (mean 74 months) and large number of surveillance colonoscopies (median, 4) than those in previous studies [11][12][13]. The incidence of metachronous cancer (1.3%) is comparable in previous reports (0.6% to 9.0%) The Korean Journal of Internal Medicine.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…[ 9 ] Furthermore, Yun et al also showed that left colon resection had a higher incidence of adenoma than right colon resection in the second surveillance colonoscopy. [ 16 ] Because the incidence of adenoma in follow-up colonoscopy was significantly higher in patients with left colon cancer (arising from the descending and sigmoid colon, as well as the distal one-third of the transverse colon) than in patients with right colon cancer (arising from the ascending colon and proximal two-thirds of the transverse colon), [ 17 ] the purpose of this study was to investigate the incidence and related factors of SSAs after left colon cancer operation.…”
Section: Discussionmentioning
confidence: 99%